ETHNOMEDICINAL PLANTS USED BY THE WANGOO PEOPLE OF BISHNUPUR DISTRICT, MANIPUR, NORTHEAST INDIA - Irom, Reena; Sarangthem, Dilipkumar Singh; O. , Hemchandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper is an attempt to survey and understand the various ethnomedicinal plants used by the Wangoo people of Bishnupur District, Manipur as medicines in the treatment of various ailments and diseases. The current issue is that there has not been much systematic study on it, particularly among the Wangoo people of Manipur, which is one of the oldest communities in the state. In the present study more than 39 indigenous medicinal plants are used by the Wangoo people in the treatment of about 34 ailments and diseases. They use both single plant and compound plants in the treatment. The significant of the study is that certain plants are believed to have multi-chemical properties in healing and curing as it differs from other neighbouring communities. Common diseases are like diarrhoea, malaria, piles, fever, snake bite, and mumps. Leaves, stems, roots and fruits are most widely used. Some of them still depends on such indigenous medicine rather than pharmaceutical medicines Assistant Professor, Department of Anthropology, Kumbi College, Kumbi, Bishnupur, Manipur